2014
DOI: 10.1016/j.ejso.2014.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The effects of neoadjuvant chemoradiotherapy on physical fitness and morbidity in rectal cancer surgery patients

Abstract: NCT01334593.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(64 citation statements)
references
References 24 publications
5
59
0
Order By: Relevance
“…Combining CPET with CT data could provide a better prediction of clinical outcome compared with either of them alone, as we found that patients with both low trueV̇O 2 peak and myosteatosis had significantly lower overall survival while low trueV̇O 2 peak only was not significantly associated with overall survival. Evidence has shown that a higher physical activity and fitness after a cancer diagnosis and its treatments reduce perioperative risk and improve quality of life and post‐operative outcomes including survival …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Combining CPET with CT data could provide a better prediction of clinical outcome compared with either of them alone, as we found that patients with both low trueV̇O 2 peak and myosteatosis had significantly lower overall survival while low trueV̇O 2 peak only was not significantly associated with overall survival. Evidence has shown that a higher physical activity and fitness after a cancer diagnosis and its treatments reduce perioperative risk and improve quality of life and post‐operative outcomes including survival …”
Section: Discussionmentioning
confidence: 99%
“…Evidence has shown that a higher physical activity and fitness after a cancer diagnosis and its treatments reduce perioperative risk and improve quality of life and post-operative outcomes including survival. 11,13,14,50,54,55 Such data raise the obvious hypothesis: Can health outcomes be improved by perioperative interventions targeted at improving body composition and physical fitness? Body composition and fitness modulation as a concept in surgical risk prediction is attractive due its potential reversibility.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have relied upon cardiopulmonary surrogates, specifically oxygen uptake, measured prior to and during exercise in assessing the physical fitness of patients. West and colleagues performed a comprehensive prospective observational study in which decreases in the level of physical fitness were demonstrated in patients' post-NACRT [71]. The authors subsequently introduced a structured responsive exercise-training program (SRETP) involving three sessions of exercise per week on a training bike, with assessments of surrogates of physical fitness.…”
Section: Management Of the Patient Post-neoadjuvant Therapymentioning
confidence: 98%